Pengaruh Lingkungan Keluarga terhadap Perkembangan Kemampuan Berbahasa Anak - Clarasita Natasya Naibaho; Fitri Aulina Tampubolon; Yenti Siburian; M. Surip (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Language skills are one of the key aspects in children's cognitive and social development. The family environment, as the first and primary environment for children, plays an important role in shaping language habits, enriching vocabulary, and developing children's communication skills. This study aims to explore the influence of the family environment on children's language development, focusing on interactions between parents and children, reading habits, and emotional support in the family. The research method used was a qualitative approach with in-depth interview techniques involving parents as research subjects. The results revealed that a communicative and supportive family environment is the main basis for children in learning language. Habits such as inviting children to talk, reading books together, and providing emotional support are the main factors that influence children's language development. In the midst of the digital era, parents need to be smart in utilizing technology, by limiting the use of gadgets and prioritizing direct interaction. Consistent communication patterns and special activities such as reading together or role-playing have also proven to be very effective in supporting children's language development. Although there are challenges such as time constraints and children's interest in gadgets, parents can overcome them with creativity and patience. This study provides practical advice for parents in creating a family environment that supports children's language development.